Human papillomavirus type 16 nucleoprotein E7 is a tumor rejection antigen. - Chen, L P (1991)
It has been speculated that immunological mechanisms play an important role in the control of carcinomas associated with human papillomavirus (HPV), such as cervical cancers. We have now demonstrated that immunization of C3H/HeN mice by syngeneic nontumorigenic fibroblast-like cells that contain the transfected HPV-16 E7 gene conferred protection against transplanted cells from a HPV-16 E7-positive syngeneic tumor. This protection was HPV-16 E7-specific and was mediated by CD8+ lymphocytes, which presumably were cytotoxic T lymphocytes. These results indicate that tumor cells containing HPV-16 E7, either as a result of transfection, as in our studies, or naturally, as occurs in many human carcinomas, can induce a tumor-specific rejection response and serve as targets for such a response. The system described here provides an animal model to further study immune responses to HPV-associated malignancies and to test the efficacy of anti-HPV vaccines toward the therapy and prevention of such tumors.